Irritable Bowel Syndrome Ameliorated Dramatically with a Plant- based Diet: A Case Report - Mitsuro Chiba; Tsuyotoshi Tsuji; Teiji Hashimoto (Iranian Journal of Colorectal Research)
Irritable bowel syndrome (IBS) is a common disease. The first-line therapy is dietary modification. However,the current recommended diets for IBS are not effective in roughly half of patients. We encountered a 28-year-old woman with IBS with diarrhea. She was referred to us by a pediatric practitioner who had been treating herbouts of diarrhea and abdominal pain since childhood. At the age of 16, in 2010, she was diagnosed with IBS.The frequency of her bowel movements was 3-4 times a day, but they became watery after meals beginningin December 2022. Routine examinations for diarrhea, including ileo-colonoscopy, were negative. She wasreceptive to trying a plant-based diet and was admitted for 9 days in mid-January. A lacto-ovo vegetarian diet(1400 kcal/day) was provided. Soon after admission, her stool normalized, and IBS symptom severity scaledecreased from 275 to 0. 1 year after discharge, she was well with normal stools. To our knowledge, there is nocase report of IBS treated with plant-based diet, and the results were dramatically effective. A plant-based diethas been known to be a healthy diet. Further investigations of plant-based diets for IBS are eagerly awaited.